Ectopic expression of human p53 inhibits entry into S phase and induces apoptosis in the Drosophila eye imaginal disc. - Yamaguchi, M.; Hirose, F.; Inoue, Y.H.; Shiraki, M.; Hayashi, Y.; Nishi, Y.; Matsukage, A. (Oncogene, 1999)
Transgenic flies in which ectopic expression of human p53 was targeted to the Drosophila eye imaginal disc were established. On sectioning of adult fly eyes which displayed a severe rough eye phenotype, most ommatidia were found to be fused and irregular shapes of rabdomeres were observed. In addition, many pigment cells were lost. In the developing eye imaginal disc, photoreceptor cell differentiation was initiated normally despite the ectopic expression of p53. However, expression of p53 inhibited cell cycle progression in eye imaginal disc cells and the S phase zone (the second mitotic wave) behind the morphogenetic furrow was almost completely abolished. Furthermore, expression of p53 induced extensive apoptosis of eye imaginal disc cells, and co-expression of baculovirus P35 in the eye imaginal disc suppressed the p53-induced rough eye phenotype. These results are consistent with the known functions of human p53 and indicate the existence of signaling systems with elements corresponding to human p53 in Drosophila eye imaginal disc cells. Genetic crosses of transgenic flies expressing p53 to a collection of Drosophila deficiency stocks allowed us to identify several genomic regions, deletions of which caused enhancement or suppression of the p53-induced rough eye phenotype. The transgenic flies established in this study should be useful to identify novel targets of p53 and its positive or negative regulators in Drosophila.